Countering Iran's Regional Strategy A Long-Term, Comprehensive Approach - Zamir, Eyal (Rowman & Littlefield Publishers, Incorporated, 2023)
In this Policy Focus, Maj. Gen. Eyal Zamir, IDF, draws on his deep experience in the Israeli military establishment to propose a detailed plan for undermining Iran's influence in the region--an approach that will preserve U.S. and Western interests, reinforce Israel and America's Arab allies, and promote regional stability